OKSIDENTALISME DALAM BUKU SUFI HEALING, TERAPI DENGAN METODE TASAWUF KARYA M. AMIN SYUKUR - -, Yuli Darwati (Bahasa Indonesia, 2024)
This study aims to determine: 1) M.Amin Syukur's critical attitude towards Sufism; 2) M. Amin Syukur's critical attitude towards medical healing; 3) M. Amin Syukur's critical attitude towards the current reality of healing. This research was conducted using qualitative research methods. The data in this study were obtained from literature review, mainly from the Sufi healing book by M. Amin Syukur and the literature on Occidentalism by Hassan Hanafi. This research uses a reciprocal inductive-deductive and/or deductive-inductive mindset. The results showed that: 1) M. Amin Syukur had a critical attitude towards Sufism. Sufism as a teaching to gain closeness to Allah SWT, can function as a healing method for both self (the Sufis), and ordinary people. This healing method is then called Sufi healing. Sufi healing as a healing method has a weakness, namely it tends to rely on scriptural texts and beliefs, on the contrary it does not have scientific references. For this reason, M.Amin Syukur conducted research to find scientific references and found them in transpersonal psychology and psychoneuroendocrinimunology; 2) M.Amin, thanks for being very critical of the west. He criticized the digital era as a product of modernity which has caused several physical and mental illnesses in society. Meanwhile, healing and medical treatment of the disease have several weaknesses, so assistance from other approaches is needed, especially psychology and spiritual approaches (Sufi healing); 3) M.Amin Syukur also has a critical attitude towards the reality of healing the disease at this time, so that he is very optimistic about the future of Sufi healing as an alternative healing in society, both in independent practice and as a companion to medical healing.